1999
DOI: 10.1074/jbc.274.8.4962
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Monocyte Tissue Factor Mediated by Tissue Factor Pathway Inhibitor and the Low Density Lipoprotein Receptor-related Protein

Abstract: Inflammatory mediators like bacterial lipopolysaccharide induce monocytes to express tissue factor (TF), the cell-surface protein that triggers the blood clotting cascade in hemostasis and thrombotic disease. The physiologic ligand for TF is the serine protease, factor VIIa (FVIIa), and the resulting bimolecular enzyme, TF/ FVIIa, can be reversibly inhibited by tissue factor pathway inhibitor (TFPI). Culturing monocytic cells in the presence of both FVIIa and TFPI caused down-regulation of TF expression via re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 65 publications
4
77
0
Order By: Relevance
“…Previous publications also indicate that TF has a higher turnover rate compared with EGFR and HER2. Hamik and colleagues demonstrated that the halflife of TF on monocytes was 3.7 hours, which could be reduced to 1.3 hours when TF was bound by TF protein inhibitor and FVII (38). Unstimulated EGFR and HER2 on the other hand have a half-life of 6 to 24 hours depending on the cell line used (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications also indicate that TF has a higher turnover rate compared with EGFR and HER2. Hamik and colleagues demonstrated that the halflife of TF on monocytes was 3.7 hours, which could be reduced to 1.3 hours when TF was bound by TF protein inhibitor and FVII (38). Unstimulated EGFR and HER2 on the other hand have a half-life of 6 to 24 hours depending on the cell line used (39).…”
Section: Discussionmentioning
confidence: 99%
“…TFPI does not cleave readily, and prevents the complex from engaging other molecules [5]. TFPI also causes monocytes to internalise and degrade TF-FVIIa complexes on the cell surface [43]. Circulating TFPIFxa-TF-FVIIa complexes are metabolised by the liver [35].…”
Section: ó 2004 Blackwell Publishing Ltdmentioning
confidence: 99%
“…FVIIa bound to TF is internalized in many cell types (e.g. fibroblasts, monocytes, and baby hamster kidney [BHK] cells) (14)(15)(16). The majority of internalized FVIIa enters the endocytotic pathway and gets degraded but a small portion of it is recycled back to the cell surface as intact protein (14).…”
Section: Fviia Association With Tf-expressing Cellsmentioning
confidence: 99%
“…Although both FVIIa and active siteinhibited FVIIa (ASIS) bind to TF, there seems to be subtle differences between them in their internalization and recycling patterns (17). Interestingly, despite the continuous internalization of FVIIa via TF, TF levels on the cell surface remain relatively constant (14)(15)(16). It may be important to note that the rate of TF-mediated FVIIa endocytosis is not as rapid as one would expect for classical receptor-mediated endocytosis.…”
Section: Fviia Association With Tf-expressing Cellsmentioning
confidence: 99%
See 1 more Smart Citation